Physical and electrical characterization of sol-gel derived BaxSr1-xTiO3 thin films of various composition ratios and thicknesses - Nurhafizah Ramli (School of Microelectronic Engineering, 2011)
The main objective of this work is to study the physical and electrical properties of BST thin films by using sol-gel technique.